Manajemen Biaya untuk Meningkatkan Ketepatan Penghitungan Biaya melalui Biaya Berbasis Aktivitas - Agung Listiadi (BISMA (Bisnis dan Manajemen), 2018)
Cost is an important factor in ensuring the company win in the competition on the market. Consumers will choose a manufacturer that is able to produce products and services that have high quality with low prices. Costs of Management Systems Contemporary emphasis on search than the allocation. And management based activities are at the heart of contemporary operating control system. At least two major factors that must be considered in the selection of cost driver (cost driver) are: the cost of measurement and the degree of correlation between the consumption cost driver with the actual overhead. Cost driver is divided into two categories, namely the structural cost driver and executional cost driver. Cost driver is the basis used to charge collected on cost pool to the product. So that the calculation of the cost through Time Driven activity-based costing system, the company obtain more precise information and accurate.